Analisis Strategi Pelayanan Islami Dalam Meningkatkan Kepuasan Pelanggan di CV.ISIPA “Pusat Rehabilitasi” Kota Jambi - Vika Gustiani; Kemas Imron Rosadi; Eri Nofriza (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the implementation of Islamic service strategies in improving customer satisfaction at CV. ISIPA Rehabilitation Center, Jambi City. The study is motivated by the importance of service quality in creating customer satisfaction, particularly in rehabilitation service companies that require high levels of trust, professionalism, and empathy. The Islamic service strategy is based on the principles of shidiq (honesty), amanah (trustworthiness), tabligh (communicativeness), and fathanah (professionalism) as the implementation of Islamic business ethics in service activities. This research employed a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation. The informants consisted of the owner, employees, and customers of CV. ISIPA Rehabilitation Center. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings reveal that CV. ISIPA has implemented Islamic service strategies in its customer service process. The principle of shidiq is reflected in honest and transparent information delivery, amanah in fulfilling service commitments responsibly, tabligh in effective communication with customers, and fathanah in the competence and professionalism of employees in providing solutions to customer needs. The implementation of these Islamic service principles contributes positively to customer satisfaction as reflected in the SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. However, several challenges remain, including limited responsiveness of some employees, less effective communication, and perceptions of unequal treatment among customers. Therefore, continuous improvement in human resource competencies, Islamic-based service excellence training, and regular service evaluations are necessary to enhance service quality and customer satisfaction.